The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1590/1414-431x20198417
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disorders in Brazil: the contribution of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: Thyroid disorders are common diseases, both in Brazil and worldwide. The Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) is a prospective cohort study that investigates cardiovascular diseases, diabetes, and associated factors, including non-classical cardiovascular risk factors such as thyroid function. Thyroid function was classified according to thyrotropin stimulating hormone (TSH), free thyroxine (FT4), and use of medication to treat thyroid disorders, after excluding participants who reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…35,36 In view of patients with T2DM with no evidence of thyroid disease, Giandalia et al 37 demonstrated that higher values of TSH within normal range were more frequent in women and younger patients and were associated with visceral obesity and higher triglyceride concentrations-two well-known CVD risk factors, although in this study, no CV outcomes were evaluated. Considering CIMT and thyroid function, in the Elsa Brazil study, 38 after a multivariate adjustment for sociodemographic and CVR factors, subclinical hypothyroidism was associated with higher CIMT values using euthyroid subjects as the reference. However, in other studies, the authors observed that thyroid hormone was not predictive of carotid atherosclerosis when adjusted for confounders, 39 and no significant relationship between CIMT and serum TSH levels was observed in normal, nonthyroxine-taking subjects.…”
Section: Overview Of Demographic and Laboratory Data Of The Studied Pmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 In view of patients with T2DM with no evidence of thyroid disease, Giandalia et al 37 demonstrated that higher values of TSH within normal range were more frequent in women and younger patients and were associated with visceral obesity and higher triglyceride concentrations-two well-known CVD risk factors, although in this study, no CV outcomes were evaluated. Considering CIMT and thyroid function, in the Elsa Brazil study, 38 after a multivariate adjustment for sociodemographic and CVR factors, subclinical hypothyroidism was associated with higher CIMT values using euthyroid subjects as the reference. However, in other studies, the authors observed that thyroid hormone was not predictive of carotid atherosclerosis when adjusted for confounders, 39 and no significant relationship between CIMT and serum TSH levels was observed in normal, nonthyroxine-taking subjects.…”
Section: Overview Of Demographic and Laboratory Data Of The Studied Pmentioning
confidence: 99%
“…The patients were recruited into a single tertiary care center with only internal validity. Only one TSH/Free T4 sample was collected for the determination of thyroid function, as has been done in other studies evaluating thyroid function 38 and the determination of antiperoxidase antibodies was not performed. Another potential limitation was the reliance on self-reported FH of premature CAD and of thyroid disease, although most studies addressed this in the same way.…”
Section: Overview Of Demographic and Laboratory Data Of The Studied Pmentioning
confidence: 99%
“…Thyroid disease is common not only in Pakistan but also all over the world. 1 Factors associated with increased incidence depend upon iodine status, but also on advancing age, gender, ethnical group and geographical area. 2,3 Its rising incidence is also associated with highest mortality rate annually as compared to all other endocrine cancers.…”
Section: Introductionmentioning
confidence: 99%